The post man - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
I estimate that 96 of our four hundred members take a good look at Spore, the ones who can read French. The other members are farmers who only speak their mother tongue of Créole. Our Association s Post Office box is 54 kilometres away. I often...